Quality versus Risk-of-Bias assessment in clinical research - Luis Furuya-Kanamori (477124) (2021)
Assessment of internal validity safeguards implemented by researchers has been used to examine the potential reliability of evidence generated within a study. These safeguards protect against systematic error, and such an assessment has traditionally been called a quality assessment. When the results of a quality assessment are translated through some empirical construct to the potential risk of bias, this has been termed a risk of bias assessment. The latter has gained popularity and is commonly used interchangeably with the term quality assessment. This key concept paper clarifies the differences between these assessments and how they may be used and interpreted when assessing clinical evidence for internal validity. Other Information Published in: Journal of Clinical Epidemiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jclinepi.2020.09.044